2005
DOI: 10.1016/j.lungcan.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of paclitaxel in advanced bronchioloalveolar carcinoma (EORTC trial 08956)

Abstract: SummaryPurpose: The incidence of bronchioloalveolar carcinoma (BAC) has risen steadily over the last decades along with the increasing frequency of adenocarcinomas. BAC is relatively resistant to commonly used chemotherapy regimens. A phase II study with single agent paclitaxel in patients with stages IIIB, IV or recurrent BAC was performed.Experimental design: Patients with BAC with at least one target bidimensionally measurable lesion staged as unresectable stages IIIB, IV or recurrent disease, not previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Our DCR and PFS results were similar to those previously reported in an advanced BAC population [4,5,[7][8][9][10][11]. DCR did not differ between therapeutic arms or pathological subtypes, although there was a strong interaction between treatment effect (arm E versus CP) on PFS and mucinous and NM subtypes (p=0.009) (figure 3), as previous studies have suggested [10].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our DCR and PFS results were similar to those previously reported in an advanced BAC population [4,5,[7][8][9][10][11]. DCR did not differ between therapeutic arms or pathological subtypes, although there was a strong interaction between treatment effect (arm E versus CP) on PFS and mucinous and NM subtypes (p=0.009) (figure 3), as previous studies have suggested [10].…”
Section: Discussionsupporting
confidence: 90%
“…Only two nonrandomised phase II trials had previously investigated the efficacy of paclitaxel monotherapy, administered every 3 weeks [4,5], but the low response rates and unacceptable toxicity reported by the Southwest Oncology Group (SWOG) 9714 trial defined this approach as ill adapted [5]. Pemetrexed monotherapy has recently achieved promising results in the Intergroupe Francophone de Cancérologie Thoracique (French Cooperative Thoracic Intergroup (IFCT)) 0401 trial [6] and in one prematurely closed phase II trial [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, the World Health Organization updated its classification and redefined bronchioloalveolar carcinoma (BAC) as being restricted to noninvasive tumors. Since this reclassification, prognostic features of patients with newly defined BAC have not been well defined, in spite of the fact that the disease appears to have a distinct clinical course and response to treatment (2,3). Although typically resistant to traditional chemotherapies, BAC is highly sensitive to EGFR-TKIs such as erlotinib and gefitinib.…”
Section: Introductionmentioning
confidence: 99%
“…Median survival was 8.6 months and 1-year survival was 35.0% (95% CI 14.1-55.8). Paclitaxel was manageable but with limited efficacy [53].…”
Section: Chemotherapymentioning
confidence: 99%